APPROACHES TO THE DEVELOPMENT OF KEY COMPETENCIES OF THE 21ST CENTURY IN THE NATIONAL RESEARCH UNIVERSITY HIGHER SCHOOL OF ECONOMICS - Znak, Natalia; Sedova, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The question of transformation of the Russian education, so that it better meets the requirements of the new reality, is more acute than ever. The aim of the study is a system of educational tools that implement individual trajectories in the National Research University Higher School of Economics (HSE) undergraduate program to form the key competences of the 21st century. The subject of the study are the methods of developing key competencies in the implementation of the “Minors” program and the “Bachelor+” program. The study was based on surveys and interviews with representatives of the administration, organizers of minors, organizers of additional programs and students of 2,3 and 4 courses (634 students). The data were processed by structuring, generalizing and then analyzing. The results of the research revealed an unambiguous positive aspect of the introduction of programs for the development of key competencies, especially communications. A new research question has been formulated. Directions for further research are suggested.